Single-Port Laparoscopic Surgery for Adnexal Mass Removal During Pregnancy: The Initial Experience of a Single Institute - Han, Ling; Wan, Qi; Chen, Yali; Zheng, Ai (Frontiers in Medicine, 2022)
Objective Single-port laparoscopy has become a feasible and safe approach for the management of benign adnexal masses during pregnancy. To our knowledge, there are few reports on the feasibility and safety of single-port laparoscopy for adnexal mass removal during pregnancy. Our study reports the use of single-port laparoscopy in adnexal mass removal during pregnancy in our hospital. Methods We included 10 cases of single-port laparoscopic surgery for adnexal mass removal during pregnancy in the West China Second University Hospital between January 2017 and March 2020. Median values were found using SPSS20. When the p-value was <0.05, the median and interquartile range were used. All patients provided informed consent. Results The following median values were recorded: surgical time, 112.50 min; blood loss, 25 ml; postoperative hospital stay, 3 days; postoperative pain [visual analog scale (VAS)] at 6 h, 3; and postoperative pain (VAS) at 24 h, 2. Our study reported no postoperative spontaneous abortions. There was one preterm birth. Conclusion Single-port laparoscopy appears to be safe for both the mother and the fetus.